Value Co-creation in Third-Party Managed Virtual Communities and Brand Equity - Rubio, Natalia; Villaseñor, Nieves; Yagüe, MªJesús (Frontiers in Psychology, 2020)
Value co-creation continues to be a key issue in the era of marketing 4.0. Despite an increasing amount of research on value co-creation, there is still a lot of ambiguity in the use of certain terms. For example, different names are used to refer to the same concept. Even though the concept of co-innovation or co-production has nearly the same meaning as co-creation, there are certain differences between them that must be clarified. In addition, another difficulty found in the literature is that the co-creation concept is frequently applied to different objects of study, such that it might be dealing with brand value co-creation, co-creation of experience, co-creation attitude, etc. In order to clarify these issues, this paper presents a brief review of the relevant literature on value co-creation.